Evaluation of Whatman FTA cards for the preservation of yellow fever virus RNA for use in molecular diagnostics - Davis, Emily H.; Velez, Jason O.; Russell, Brandy J.; Basile, A. Jane; Brault, Aaron C.; Hughes, Holly R. (PLoS neglected tropical diseases, 2022)
Yellow fever virus (YFV) is a flavivirus that frequently causes outbreaks of hemorrhagic fever in Africa and South America and is considered a reemerging public health threat. Accurate diagnosis of yellow fever (YF) disease is critical as one confirmed case constitutes an outbreak and may trigger a mass vaccination campaign. Highly sensitive and specific molecular diagnostics have been developed; however, these assays require maintenance of cold-chain during transport of specimens to prevent the degradation of viral RNA prior to testing. Such cold-chain requirements are difficult to meet in some regions. In this study, we investigated Whatman FTA cards as an alternative stabilization method of YFV RNA for use in molecular diagnosis. Using contrived specimens, linear regression analysis showed that RNA detection from a single 6mm FTA card punch was significantly less sensitive than traditional RNA extraction; however, pooling RNA extracted from two FTA punches significantly lowered the limit of detection to be equal to that of the traditional RNA extraction gold standard. In experiments addressing the ability of FTA card methodology to stabilize YFV RNA at variable temperature, RNA could be detected for more than two weeks following storage at 25°C. Even more promising, YFV RNA was detectable on cards held at 37°C from two days to over two weeks depending on viral input. FTA cards were also shown to stabilize YFV RNA at high humidity if cards were desiccated prior to inoculation. These results support that FTA cards could be cost effective and easy to use in molecular diagnosis of YF, preserving viral RNA to allow for positive diagnoses in situations where maintaining cold-chain is not feasible.